Stabilization of Palygorskite Aqueous Suspensions Using Bio-Based and Synthetic Polyelectrolytes - Ferraz, Eduardo (2021)
Palygorskite is a natural fibrous clay mineral that can be used in several applications, for which colloidal stability in aqueous suspensions is a key point to improve its performance. In this study, methods of magnetic stirring, high-speed shearing, and ultrasonication, as well as different chemical dispersants, combined with these methods, namely carboxymethylcellulose, alginate, polyphosphate, and polyacrylate, were used to improve the dispersibility and the formation of stable suspensions of palygorskite in different conditions of pH. The stability and particle size of suspensions with a low concentration of palygorskite were evaluated by visual inspection, optical and electron microscopy, dynamic light scattering, and zeta potential measurements. Moreover, the palygorskite used in this work was initially characterized for its mineralogical, chemical, physical, and morphological properties. It was found that more stable suspensions were produced with ultrasonication compared to the other two physical treatments, with magnetic stirring being inefficient in all tested cases, and for higher pH values (pH of 12 and pH of 8, the natural pH of the clay) when compared to lower pH values (pH of 3). Remarkably, combined with ultrasonication, carboxymethylcellulose or in a lesser extent polyphosphate at near neutral pH allowed for the disaggregation of crystal bundles of palygorskite into individualized crystals. These results may be helpful to optimize the performance of palygorskite in several domains where it is applied.